Human embryonic stem cell-derived endothelial cell product injection attenuates cardiac remodeling in myocardial infarction - Spiroski, Ana-Mishel; McCracken, Ian R.; Thomson, Adrian; Magalhaes-Pinto, Marlene; Lalwani, Mukesh K.; Newton, Kathryn J.; Miller, Eileen; Bénézech, Cecile; Hadoke, Patrick; Brittan, Mairi; Mountford, Joanne C.; Beqqali, Abdelaziz; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Mechanisms contributing to tissue remodelling of the infarcted heart following cell-based therapy remain elusive. Whilst cell-based interventions have the potential to influence the cardiac healing process, there is little direct evidence of preservation of functional myocardium. Aim: To investigate tissue remodelling in the infarcted heart following human embryonic stem cell-derived endothelial cell product (hESC-ECP) therapy. Methods: Following coronary artery ligation (CAL) to induce cardiac ischaemia, we investigated infarct size at 1-day post-injection in media-injected controls (CALM, n=11), hESC-ECP-injected mice (CALC, n=10), and dead hESC-ECP-injected mice (CALD, n=6); echocardiography-based functional outcomes 14 days post-injection in experimental (CALM, n=13; CALC, n=17) and SHAM surgical mice (n=4), and mature infarct size (CALM and CALC, both n=6). We investigated ligand receptor interactions (LRIs) in hESC-ECP cell populations, incorporating a publicly available C57BL/6J mouse cardiomyocyte-free scRNAseq dataset with naïve, 1- and 3-day post-CAL hearts. Results: hESC-ECP injection reduces infarct area (CALM: 54.5±5.0%, CALC: 21.3±4.9%), end diastolic (CALM: 87.8±8.9uL, CALC: 63.3±2.7uL) and end systolic ventricular volume (CALM: 56.4±9.3uL, CALC: 33.7±2.6uL). LRI analyses indicate an alternative immunomodulatory effect mediated via viable hESC-ECP-resident signalling. Conclusions: Delivery of the live hESC-ECP following CAL modulates the wound healing response during acute pathological remodelling, reducing infarct area and preserving functional myocardium in this relatively acute model. Potential intrinsic myocardial cellular/hESC-ECP interactions indicate that discreet immunomodulation could provide novel therapeutic avenues to improve cardiac outcomes following myocardial infarction.